“It’s about Complete Incorporation”: An Interview with Barbara Hannigan - Bernstein, Tamara (Circuit, 2020)
In a conversation with Tamara Bernstein, Canadian soprano Barbara Hannigan discusses topics related to her musical formation and early career, significant professional relationships, and the professional voice. Hannigan describes her early decision to specialize in contemporary music as a moment of quasi-religious vocation; she recounts the artistic processes of composers George Benjamin and Hans Abrahamsen when they were writing opera roles for her, and reflects on the influence of some of her colleagues and mentors, including the late Reinbert de Leeuw and three stage directors. She elaborates on the transformative experience of performing the title character of Alban Berg’s Lulu; addresses the persistent prejudice against singers who specialize in contemporary music; and comments on approaches to vibrato in both contemporary and “early” music. Her observations on the implications of ageing for an elite singer speak to the intimate physical connection of an artist to her voice, and confirm Hannigan’s fundamental commitment to singing as “complete incorporation.”